International security (MIT Press, 1976)
nternational Security publishes lucid, well-documented essays on the full range of contemporary security issues. Its articles address traditional topics such as war and peace, as well as more recent dimensions of security, including the growing importance of environmental, demographic, and humanitarian issues, and the rise of global terrorist networks. International Security has defined the debate on US national security policy and set the agenda for scholarship on international security affairs for more than thirty years. For many years, International Security has been consistently at or near the top of the Thomson Reuters Impact Factor rankings of all international relations journals.